Selenium-rich yeast attenuates ochratoxin A-induced small intestinal injury in broiler chickens by activating the Nrf2 pathway and inhibiting NF-KB activation. (March 2020) - Tong, Cui; Li, Peng; Yu, Li-Hui; Li, Lin; Li, Kang; Chen, Yueli; Yang, Shu-Hua; Long, Miao
Graphical abstract: Highlights: OTA induce small intestinal injury in broiler chickens. Selenium-rich yeast attenuates Ochratoxin A toxicity. The Nrf2 pathway and NF-KB pathway were involved in SeY protect OTA-induced toxicity. Abstract: The aim was to investigate whether selenium-enriched yeast (SeY) can attenuate intestinal injury in broiler chickens induced by ochratoxin A (OTA). Here, the results showed that SeY addition increased the body weight, feed conversion ratio, villi height, villus/crypt ratio, and the numbers of goblet cells. Furthermore, the levels of oxidative stress by SeY addition (superoxide dismutase activity, total antioxidant capacity, and total glutathione content) were significantly decreased (P < 0.01), but the malondialdehyde content was significantly increased (P < 0.05). Moreover, nuclear transcription factor-κB (NF-κB), interleukin-1beta and tumor necrosis factor-α mRNA expressions were significantly decreased (P < 0.01) by SeY addition, but nuclear factor erythroid-2 related factor 2 (Nrf2) and heme oxygenase-1 were significantly increased (P < 0.05). In addition, western blotting results indicated that SeY normalized the OTA-induced phosphorylation of NF-κB and Nrf2. In summary, SeY alleviates OTA-induced intestinal toxicity in broiler chickens by activating the Nrf2 pathway and inhibiting NF-κB activation.